Experimental Verification of Single Phase Z Source Inverter for Photovoltaic Applications - Saravanan Vasudevan; M. Aravindan; V. Balaji; M. Arumugam (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
A single phase Z source inverter is developed for better voltage boosting and inversion ability suited for photovoltaic power generation systems. The operation of the Z source inverter is described with relevant equations. Simple boost scheme is used for switching actions of the inverter. The performance of the inverter used for photovoltaic applications can be checked with simulation and experimental results, which prove that it has single-stage buck and boost capability and improved reliability.